2011
DOI: 10.4103/0973-029x.80024
|View full text |Cite
|
Sign up to set email alerts
|

Oral lesions associated with nevirapine-related Stevens Johnson syndrome: A report of four cases

Abstract: Nevirapine is a non-nucleoside reverse transcriptase inhibitor, widely used in combination with other antiretroviral agents for treatment of HIV infection. Steven Johnson syndrome (SJS) is the major toxicity of nevirapine. We describe here four cases of SJS in HIV seropositive patients following nevirapine therapy. In all four cases cutaneous hypersensitivity reaction was seen with extreme oral lesions, three patients presented clinically with elevated liver enzymes and hepatitis, and two patients had ocular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Earlier studies [56] (Table 4), have reported increased total bilirubin, conjugate and unconjugated bilirubin as well as elevated levels of cholesterol following NVP administration, pointing towards hepatotoxicity. Result is in line with earlier reports of elevated levels of bilirubin following NVP based treatments [49,52]. Fatal hepatotoxicity including fulminant and cholestatic hepatitis, hepatic necrosis and hepatic failure had also been reported in patients with NVP treatment [7,47,51,53,55,57,58] Increases in liver enzyme (ALT, AST, ALP and GGT) levels imply that NVP administration may impair liver, hamper the integrity and function of the liver in individual users.…”
Section: Effect Of Nvp On Serum Liver Enzymes Profilesupporting
confidence: 79%
“…Earlier studies [56] (Table 4), have reported increased total bilirubin, conjugate and unconjugated bilirubin as well as elevated levels of cholesterol following NVP administration, pointing towards hepatotoxicity. Result is in line with earlier reports of elevated levels of bilirubin following NVP based treatments [49,52]. Fatal hepatotoxicity including fulminant and cholestatic hepatitis, hepatic necrosis and hepatic failure had also been reported in patients with NVP treatment [7,47,51,53,55,57,58] Increases in liver enzyme (ALT, AST, ALP and GGT) levels imply that NVP administration may impair liver, hamper the integrity and function of the liver in individual users.…”
Section: Effect Of Nvp On Serum Liver Enzymes Profilesupporting
confidence: 79%
“…In the Women and Infants Transmission Study (WITS) cohort (1989)(1990)(1991)(1992)(1993)(1994) artificial rupture of membranes (RR 1.06; 95 % CI 0.74-1.53) and exposure to blood during labour (RR 0.7; 95 % CI 0.4-1.27) or delivery (RR 1.06; 95 % CI 0.74-1.52) were not associated with transmission [38]. Also, fetal skin lesions (RR 1.2; 95 % CI 0.7-1.8) and episiotomy/tear (RR 1.0; 95 % CI 0.7-1.3) have not been associated with transmission [39,27].…”
Section: Management Of Labour and Deliverymentioning
confidence: 93%
“…Bone disorders as osteopenia, osteoporosis and osteonecrosis have all been documented. Nevirapine has been associated with mucus membrane /skin eruptions, including Steven Johnson's syndrome [27]. It is therefore essential to monitor haematological and clinical chemistry parameters for patients on antiretroviral.…”
Section: Antiretroviral Treatment In Pregnancymentioning
confidence: 99%
“…The spectrum of severe cutaneous adverse drug reactions includes SJS or TEN, hypersensitivity syndrome (HSS), anaphylaxis and angioedema, serum sickness, and cutaneous vasculitis. One of the undesirable side-effects of highly active anti-retroviral therapy (HAART) in HIV management is SJS [6]. Mycoplasma pneumonia infection has also been reported in association with SJS [7].…”
Section: Discussionmentioning
confidence: 99%